«Nos traen tan avasallados hasta quitarnos nuestro señorío»: cabildos mayas, control local y representación legal en el Yucatán del siglo XVI - Cunill, Caroline (2016)
In Spanish Colonial America, as well as in the Iberian Peninsula at the same time, different jurisdictions intertwined in the same space. By way of consequence, the complex political organization of the New World was composed, at the local level, by the Indian and Spanish Councils, the doctrines, and the provincial structures called corregimientos. Although the officials of those institutions received precise instructions, in which the Spanish Crown defined and limited their functions, tensions were common between the Indian governors, the clergymen, the Spanish Councils’ officeholders, and the Spanish provincial magistrates, or corregidores. The present article will analyze a series of lawsuits that occurred in sixteenth century Yucatan and in which those authorities were implicated, in order to highlight not only the nature of the jurisdictional conflicts, but also the modalities of their resolution at stake in the Spanish Empire’s courts of justice. Special emphasis will be put on the jurisdiction of the Maya Councils with the objective of better understanding the scope of indigenous agency in Spanish Colonial America. We argue that the local control on the one hand, and the legal representation on the other, were key elements in these processes.